Photomorphogenesis and content of carbohydrates in the axial organs of field pean seedlings under the influence of selective light - Zhmurko, V. V.; Avksentieva, O. O.; Batuieva, Y. D. (Biophysical Bulletin, 2022)
Background: Light is a multifaceted exogenous factor that plays an important role in plant growth and development. The spectral composition of light is determinative for the regulation of photomorphogenetic processes in plants. Nowadays plants have several groups of photoreceptors that include receptors of red (RL) and far red light (FRL) — phytochromes; receptors of UV-A, blue (BL) and green (GL) light — cryptochromes, phototropins, proteins of the ZEITLUPE family, as well as the UV-B receptor — UVR8 protein. One of the possible mechanisms that realize an activation of photoreceptor systems in the plant may be concerned with carbohydrate metabolism. The research of morphogenetic reactions of seedlings under the action of selective light irradiation by activating photoreceptor systems is important for understanding the mechanisms of regulation of the program of plant organism`s ontogenesis.The aim of this study was to investigate the effect of selective light of different spectrum: RL (660 nm), GL (530 nm) and BL (450 nm) on growth reactions, morphogenesis and content of soluble carbohydrate in axial organs of seedlings of long-day plants.Materials and methods: 10-day etiolated seedlings of pea Maecenat variety were used for experiments. Activation of photoreceptor systems by red (RL, 660nm), green (GL, 530nm) and blue (BL, 450nm) light was performed for 5 days for 30 minutes using LED matrices. The growth reaction, morphogenesis and the content of soluble mono- and oligosugars in the axial organs of seedlings were analyzed.Results: The axial organs of seedlings differ in their response to irradiation with selective light. The root system is more sensitive to the action of selective light than the shoot of the seedlings of the long-day plants of the pea Maecenat variety. Activation of photoreceptor systems stimulates growth processes, activates the processes of photomorphogenesis and the biosynthesis of oligosugars de novo, most likely sucrose. Among the spectra of selective light, the maximum stimulating effect is shown by irradiation of the GL (530 nm) in the reactions of the aboveground part and roots. RL (660 nm) and BL (450 nm) show opposite effects: RL initiates a photomorphogenetic program of shoot part, and BL has a greater effect on photomorphogenesis of root system.Conclusions: Different levels of growth, morphogenetic processes and changes in the content of soluble carbohydrates are probably related to the ability of photoreceptor systems to activate the realization of different ways of photomorphogenesis in the axial organs of seedlings under the influence of selective light of a certain spectrum.